A framework of parenting leadership styles and students achievement elements - Khairunesa Isa; Syamimi Afiqah Shahlal; Sarala Thulasi Palpanadan; Nurul Sabrina Zan; Jalihah Md Shah (Academic Inspired Network, 2024)
Parenting leadership style has an impact on student achievement. This study explores the relationship between parenting leadership styles and student achievement through the development of a comprehensive framework. This framework is developed through a thorough examination and analysis of previous studies on parental leadership style and its impact on student academic performance. By investigating various parenting leadership paradigms, including authoritative, authoritarian, permissive, and neglectful styles, and their impact on student outcomes, this research aims to describe a clearer understanding of the leadership style of parents that is practiced in producing excellent students. The findings indicate that parenting leadership styles exert varying effects and influences on achievement; however, authoritative leadership style emerges as the predominant parental approach among student parents and significantly correlates with students' academic achievement. This study hopes to contribute to SDG 3 Good Health and Well-being where parenting styles can significantly impact children's socio-emotional well-being and mental health, which are critical components of overall health and well-being. Understanding the relationship between parenting leadership styles and student achievement can inform strategies to promote positive mental health outcomes among students.